Tributação e igualdade: raça, pobreza e neutralidade - Chagas, Vitória Medeiros de Melo Caballero (2024)
The purpose of this study is to demonstrate that the current structure of the Brazilian Tax System does not comply with the principle of equality, as it burdens people who are more socioeconomically vulnerable in a proportionally higher way. Furthermore, the study aims to prove that the Brazilian Tax System also disrespects the principle of equality when is analyzed from a racial perspective, since black people usually pay proportionally more taxes than white people. For this purpose, this work is based on quantitative and qualitative research, using statistical studies and bibliographical works, which will demonstrate that the Brazilian Tax Law violates the essence of the constitutional principles that inform tax activity, according to which all taxpayers in a similar position should be submitted to the same tax treatment. Possible differentiations are only justified for the protection of individuals in a situation of greater socio-economic vulnerability or for the achievement of goals that are important to the Federal Constitution. At the end of the study, possible solutions to the problem are presented